1989
DOI: 10.1016/0014-5793(89)80258-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of BlaI, the repressor for the β‐lactamase gene of Bacillus licheniformis, with the blaP and blaI promoters

Abstract: BlaI repressor for the fl-lactamase gene (blaP) of Bacillus licheniformis 749, was shown to repress expression of blaP and of the repressor gene (blal), using the purified protein in a DNA-directed in vitro translation assay. Binding of Blal to the promoter regions of blaP and blal was examined by equilibrium and competitive binding assays. BlaI binds to the blaP promoter with an equal or only slightly higher affinity than to the blal promoter. DNase I footprinting shows that BlaI binds directly to the blaP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…We therefore conclude that other members of the MecI/BlaI repressor family probably contact their cognate operators and those related ( Fig. 2A) (16,47,48), bla from S. aureus (13,29), and mec from MRSA (11,12,29). In each case, the promoter regions affected are indicated, as well as the GenBank TM sequence accession numbers (in parentheses) and the position within the nucleotide sequence.…”
Section: Structure Of Methicillin Repressor Within the Complex-likementioning
confidence: 82%
“…We therefore conclude that other members of the MecI/BlaI repressor family probably contact their cognate operators and those related ( Fig. 2A) (16,47,48), bla from S. aureus (13,29), and mec from MRSA (11,12,29). In each case, the promoter regions affected are indicated, as well as the GenBank TM sequence accession numbers (in parentheses) and the position within the nucleotide sequence.…”
Section: Structure Of Methicillin Repressor Within the Complex-likementioning
confidence: 82%
“…le. brane receptor, BlaRl, binds a,-lactam compound and transmits a signal to the cytoplasm that relieves repression by Blal of the 13-lactamase promoter. Mutations affecting blaI cause high-level constitutive,-lactamase synthesis (8,16,30).…”
Section: Resultsmentioning
confidence: 99%
“…RN24, derived from RN11, is a constitutive, high-level producer of ,B-lactamase because of a mutation in the 3-lactamase repressor (blal) gene (8,16). RN6390B is a wild-type (agr+) strain, RN6911 is an agr null strain (10,17), and RN6734 is a derivative of RN6390B that does not produce beta-hemolysin because of lysogenization with phage 413, which inserts within the beta-hemolysin structural gene (6).…”
Section: Methodsmentioning
confidence: 99%
“…In this regulatory system PenI binds to three operators within the region containing the divergent promoters for penI and penP (Grossman and Lampen, 1987;Himeno et al, 1986;Salerno and Lampen, 1988). PenI represses penP by preventing the initiation or elongation of the mRNA and similarly the synthesis of PenI is autoregulated (Wittman and Wong, 1988;Grossman et al, 1989). It has been shown that PenI is present as a dimer in solution, that the DNA-binding function is located near the N-terminus and that the dimerization function is in the C-terminal region (Wittman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%